2014
DOI: 10.1063/1.4891874
|View full text |Cite
|
Sign up to set email alerts
|

Growth of GaAs1−xBix by molecular beam epitaxy: Trade-offs in optical and structural characteristics

Abstract: Recent work has shown that Bi incorporation increases during molecular beam epitaxy (MBE) when surface processes are kinetically limited through increased growth rate. Herein we explore how the structural and optical properties of GaAs1−xBix films are modified when grown under conditions with varying degrees of kinetic limitations realized through growth temperature and growth rate changes. Within the typical window of MBE growth conditions for GaAs1−xBix, we compare films with similar (∼3%) compositions grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Interestingly, investigations on LCMs in other III-V semiconductor alloys have established a correlation between the modulation wavelength K and the atom surface diffusion length k, 17,18 where K increases with increased k. In a rough approximation, K / k. 18 In the case of III-V-Bi compounds, there is a lack of data regarding atomic surface diffusion lengths, with only few works commenting on the topic. 19,20 The same is true for LCMs in bismide alloys. 11 Furthermore, it is unclear whether K is determined by k Ga , k As , or k Bi .…”
Section: Resultsmentioning
confidence: 82%
“…Interestingly, investigations on LCMs in other III-V semiconductor alloys have established a correlation between the modulation wavelength K and the atom surface diffusion length k, 17,18 where K increases with increased k. In a rough approximation, K / k. 18 In the case of III-V-Bi compounds, there is a lack of data regarding atomic surface diffusion lengths, with only few works commenting on the topic. 19,20 The same is true for LCMs in bismide alloys. 11 Furthermore, it is unclear whether K is determined by k Ga , k As , or k Bi .…”
Section: Resultsmentioning
confidence: 82%
“…The resultant hole concentration is found to correlate with PL emission efficiency. In our previous study, 16 we found that higher growth temperature and lower growth rate can enhance PL emission efficiency, and herein, we show that these growth conditions also enhance the hole concentration.…”
Section: -mentioning
confidence: 99%
“…More information on these samples can be found in our previous work. 16 Typical GaAs 1−y Bi y Raman spectra can be found in two prior studies. 9,10 Four polarized quasi-backscattering geometries can be used for the GaAs zinc blende structure:…”
Section: -13mentioning
confidence: 99%
See 1 more Smart Citation
“…A general method for overcoming the poor solubility of Bi atoms in MBE grown III-V compounds is to grow the material at a low temperature and at a low V/Bi flux ratio [9,34,35]. Unfortunately, these growth conditions favor the formation of group-III vacancies as well as group-V related antisites or interstitials [36].…”
Section: Crystal Defects In Bi:inpmentioning
confidence: 99%